2022
DOI: 10.1002/ente.202200485
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid Gating in Perovskite Solar Cells with Fullerene/Carbon Nanotube Collectors

Abstract: Metallic cathodes are one of reasons for instability in perovskite solar cells due to reaction with halogens I−, Br−, and it is desirable to have stable carbon‐based cathodes, particularly carbon nanotubes (CNTs), and transport layers such as C60/C70. In this work, we show that gating of such top CNT cathode in ionic liquid by changing gate voltage (V g) tunes the Fermi level of CNT by electrical double layer charging and causes lowering of the barrier at C60/C70 electron transport layer (ETL). Moreover, at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 117 publications
(145 reference statements)
0
7
0
Order By: Relevance
“…By simulating an ionically gated perovskite solar cell using the DD model in our previous work, 32 we demonstrated that penetrated ions inside CNTs can raise the electrode Fermi level and convert a Schottky contact into an ohmic one through the reduction of the potential barrier at the ETL/ CNT interface. Additionally, at higher gate voltages, positive ions can drift in high concentrations inside the ETL, thereby doping it.…”
Section: Drift-diffusion Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…By simulating an ionically gated perovskite solar cell using the DD model in our previous work, 32 we demonstrated that penetrated ions inside CNTs can raise the electrode Fermi level and convert a Schottky contact into an ohmic one through the reduction of the potential barrier at the ETL/ CNT interface. Additionally, at higher gate voltages, positive ions can drift in high concentrations inside the ETL, thereby doping it.…”
Section: Drift-diffusion Modelingmentioning
confidence: 99%
“…In this study, we present an architecture similar to one recently described in our previous work . We then fabricate and characterize the internal p–i–n structure within the perovskite photoactive layer and the n-ETL/n-CNT interface controlled by a horizontal CNT ionic gate CE placed next to the PSC pixel.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since 2009, hybrid perovskites have proven to be an excellent material for optoelectronics, including solar cells (SCs), light-emitting diodes (LEDs), and various other device types. Additionally, the perovskite bandgap can be continuously tuned by incorporating different halides into its structure. By introducing chloride, bromide, and iodide in different proportions to the perovskite composition, the bandgap can be adjusted within the range of 1.5–3.2 eV .…”
Section: Introductionmentioning
confidence: 99%